Selective sphingosine-1-phosphate receptor 1 modulation ameliorates TBI-induced neurological deficit after CCI. (17th April 2021) - Qu, Xingguang; Zhang, Zhaohui; Xu, Xiaoyun; Wang, Jiahui; Lei, Chao; Zhou, Gaosheng; Wu, Wen; Huang, Lin; Chen, Xing; Yu, Su; Wang, Tao
Highlights: Treatment of RP101075 improved TBI-induced cognitive dysfunction. RP101075 remarkably reduced brain edema and brain injury volume after TBI. RP101075 can decrease the infiltration of peripheral immune cells and attenuate the expression of proinflammatory factors in the brain following TBI. Abstract: Background and Purpose: The inflammatory response after traumatic brain injury (TBI) can contribute to secondary brain injury. RP101075, a sphingosine-1-phosphate receptor modulator, can attenuate various inflammatory responses. Here, we hypothesized that consecutive administration of RP101075 over 3 days could broadly suppress the TBI-induced inflammatory response and ameliorate the outcomes of TBI. Methods and Results: Young C57/BL6 mice were subjected to a controlled cortical impact (CCI) model. RP101075-treated mice exhibited significantly reduced scores on the modified neurological severity score (mNSS) test on days 3, 7, 14, and 21 after TBI, in comparison to TBI mice that received the vehicle. RP101075-treated mice had a remarkably decreased percentage of foot faults on the foot fault test on days 7, 14, and 21 after surgery, in comparison to TBI mice that received the vehicle. Using the wet brain weight/dry brain weight method, we found that RP101075 attenuated brain edema at 3 days post-TBI. According to the results of the Morris water maze (MWM), TBI mice treated with RP101075 exhibited reduced latency time and an increased percentage of target quadrant time from day 24 to day 25 after TBI, in comparison to TBI mice that received the vehicle. In addition, flow cytometry and immunohistochemistry showed that RP101075 markedly decreased the number of infiltrated T cells, B cells and NK cells at 3 days after TBI. Analysis of Western blot data showed that RP101075 lowered the expression of proinflammatory factors on day 3 after TBI. Conclusions: Our study demonstrated that consecutive administration of RP101075 over 3 days suppressed the TBI-induced inflammatory response and ameliorated neurological deficits after TBI. Thus, this procedure may be a potential treatment strategy for TBI in the clinical setting.